Comparação de testes para análise de vigor em sementes de soja e sua relação com a emergência em campo - Santorum, Márcia (2011)
One of the biggest problems in the production of soya is to get a vigorous seed that can emerge under wide range of conditions in the field. If some factor threatens seed germination and seedling emergence, it threatens also the stand of crop. Thus, the objective of this work was to compare the tests used to identify vigor in soybean seeds relating after comparison, tests that can be used with lower cost and faster results, and establish a model that correlates seeds vigor given in the laboratory with field emergence. The work was conducted at the Laboratory for Seeds and Plants Evaluation (LASP), Unioeste - Campus Cascavel and in field at the COODETEC Central Cooperative for Agricultural Research, in Cascavel. Soybean seeds were harvested with mechanical harvesters. Five cultivars of soybeans produced in crop year 08/09 from COODETEC, under the same conditions of management and harvesting and with different morphological characteristics were used. The tests used included determination of moisture content, germination, emergence in sand, purity, immersion in sodium hypochlorite, accelerated aging, controlled deterioration, cold test, seedling growth, electrical conductivity, tetrazolium, emergence percentage and seedling length in field and seedling dry weight. The experimental design used for tests was randomized and the resulting means were compared by the Tukey test at 5% significance level. It was observed from the results that the three cultivars that stood out in most of tests also showed better field emergence. Among the analyzed tests, it can be concluded that the controlled deterioration, tetrazolium, purity, germination speed index emergence speed and emergence speed coefficient in sand showed closer to the emergency response in field. A multiple regression model was then adjusted to account for the emergence in the field, which included the emergence speed in sand (ES), the germination speed index (GSI) and the emergence speed index in sand as variables correlating better seed vigor with field emergence.